Pengaturan Rujuk Di Indonesia, Malaysia, Brunei Darussalam Dan Singapura - Mariani Mariani (Fakultas Syariah UIN Antasari, 2022)
Abstract: A period in which the divorce happens at a legal marriage where a husband makes an approachÂ to his ex-wife to make relationship as a couple of marriage (husband and wife) before her iddah period, in Islam, is called â€œRujukâ€ (reconciliation). It can be done by a husband to his ex-wife if in period of first or second divorce. In the life of Indonesian government, rujuk is regulated and protected by Indonesian regulation, that is, UU No. 32/ 1954. Besides, it is regulated in Inpres No. 1/ 1991 Chapter XVIII Article 163-169 KHI. So in Malaysia, Brunei Darussalam, and Singapore, each has its own regulation. The method used in this research is qualitative method. It is found that the regulation of reconciliation (rujuk) in Southeast Asia, especially, Indonesia, Malaysia, Brunei Darussalam, and Singapore has similarity in following fiqh madzhab, namely, Syafiâ€™i madzhab. This research also discusses the definition of rujuk according to fuqaha, implementation of rujuk according to Islamic law, rujuk in positif law in Indonesia, Malaysia, Brunei Darussalam, and SingaporeÂ Abstrak: Fase di mana terjadi perceraian pada sebuah perkawinan yang sah dan suami mendekati kembali kepada mantan isterinya untuk menjalin hubungan sebagai pasangan suami isteri sebelum masa iddahnya , dalam konsep agama disebut â€œRujukâ€, ini bisa dilaksanakanÂ oleh suami kepada isterinya , apabila masih posisi talak satu atau talakÂ dua,. Dalam kehidupan bernegara di Indonesia rujukÂ diatur dan dilindungi oleh perundang-undangan RI, yaitu Undang-undang No. 32 Tahun 1954, selain itu rujuk juga diatur dalam Instruksi Presiden No 1 Tahun 1991 Bab XVIII dalam pasal 163 sampai dengan pasal 169 KHI, begitu juga di Negara Malaysia, Brunai Darussalam dan Singapura.msing masing memiliki aturan tersendiri. .Metode yang digunakan dalamÂ penelitian ini yaitu metodeÂ deskriptif kualitatif, sehingga didapatkan hasil riset berupa Pengaturan rujukÂ di negara Asia Tenggara khususnya Malaysia, Brunai Darussalam dan Singapura memiliki kesamaan dalam penggunaan madzhab yaitu madzhab Syafiâ€™iÂ Dalam Jurnal ini juga membahas terkait pengertian rujuk menurut para ahli fiqh, teknis pelaksanaan rujuk menurut hukum Islam, Rujuk Dalam Hukum Positif, Indonesia, Malaysia, Brunai Darussalam dan Singapura